2016
DOI: 10.2174/2210289201607010153
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Candidate Vaccine Antigens Delivered Through Naked Plasmid and Mycobacterial Vectors

Abstract: Tuberculosis (TB) is a major global health problem and has been declared "a global emergency" by the World Health Organization. The failures of the currently available vaccine against TB, i.e. Mycobacterium bovis BCG, to impart consistent protection against TB, have led to the need for alternative vaccines. The low molecular weight major antigenic proteins, i.e. PE35, CFP10 and ESAT6, encoded by Mycobacterium tuberculosis-specific region of difference-1 (RD1) are among the antigens considered important to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Therefore, further studies were carried out with PE35 as the antigen for DNA vaccine development. It was shown that protective Th1-type cellular immune responses were induced in mice immunized with a PE35-based DNA vaccine construct (pUMCV6-PE35) [28,29]. However, non-protective and pathologic Th2-type and anti-inflammatory responses were not detected [30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further studies were carried out with PE35 as the antigen for DNA vaccine development. It was shown that protective Th1-type cellular immune responses were induced in mice immunized with a PE35-based DNA vaccine construct (pUMCV6-PE35) [28,29]. However, non-protective and pathologic Th2-type and anti-inflammatory responses were not detected [30].…”
Section: Introductionmentioning
confidence: 99%